Synthesis and Crystal Structure of 1,4-bis[(2’-Thenylaminoformyl)phenoxyl]methylbenzene - Wang, Li; Wang, Xiao-Run; Cheng, Guo-Quan; Peng, Yun-Qiao; Song, Xue-Qin (Asian Journal of Chemistry, 2013)
A novel salicylamide derivative i.e., 1,4-bis[(2'-thenylaminoformyl)phenoxyl]methylbenzene with the m.f. C32H28N2O4S2 has been synthesized and the crystal structure was determined by single crystal X-ray diffraction. There are strong intramolecular hydrogen bonding between the amide nitrogen atoms and the ethereal oxygen atoms which stabilized the structure to form a trans configuration. Furthermore the title compound are linked by intermolecular C9-H9…O1 hydrogen bonds into an infinite 1D chain parallel to the bc plane .